2022
DOI: 10.46298/jnsao-2022-7269
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the implicit Euler time-discretization of passive linear descriptor complementarity systems

Abstract: paper 7269 This article is largely concerned with the time-discretization of descriptor-variable systems coupled to with complementarity constraints. They are named descriptor-variable linear complementarity systems (DVLCS). More speci cally passive DVLCS with minimal state space representation are studied. The Euler implicit discretization of DVLCS is analysed: the one-step non-smooth problem (OSNSP), that is a generalized equation, is shown to be well-posed under some conditions. Then the convergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 33 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…1 with expressions in which the inertia varies between the forward-driving and backdriving cases. Here, it is shown that their results are consistent with the DAI (14) and DI (33). Under the condition |ρ| < 1, if vϕ(f u , f v , ρ) > 0, the DI (33) reduces to…”
Section: Dynamics: Apparent Inertiasupporting
confidence: 65%
See 4 more Smart Citations
“…1 with expressions in which the inertia varies between the forward-driving and backdriving cases. Here, it is shown that their results are consistent with the DAI (14) and DI (33). Under the condition |ρ| < 1, if vϕ(f u , f v , ρ) > 0, the DI (33) reduces to…”
Section: Dynamics: Apparent Inertiasupporting
confidence: 65%
“…Although a thorough mathematical analysis of such ill-posed cases is left outside the scope of the paper, one may interpret the empty-valued case as the situation where the triplet {f u , f v , v} in the DI (33) is not permitted and thus v should instantaneously reach zero with the infinite acceleration v = ±∞. The dual-valued case may be more debatable, but seeing the structure of λ in Fig.…”
Section: Dynamics: DI Representationmentioning
confidence: 99%
See 3 more Smart Citations